2021
DOI: 10.3390/ijerph18115718
|View full text |Cite
|
Sign up to set email alerts
|

Improved Inpatient Care through Greater Patient–Doctor Contact under the Hospitalist Management Approach: A Real-Time Assessment

Abstract: Objective: To examine the difference between hospitalist and non-hospitalist frequency of patient–doctor contact, duration of contact, cumulative contact time, and the amount of time taken by the doctor to resolve an issue in response to a medical call. Research Design and Measures: Data from 18 facilities and 36 wards (18 hospitalist wards and 18 non-hospitalist wards) were collected. The patient–doctor contact slip and medical call response slips were given to each inpatient ward to record. A total of 28,926… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…They also found that this situation negatively impacted communication effectiveness between doctor and patient. Although our study did not explore treatment quality, it is possible that this parameter was affected during the MCO given that time spent interacting with healthcare professionals affects treatment outcomes and patient satisfaction [95][96][97].…”
Section: Covid-19 Response Measures Among Healthcare Servicesmentioning
confidence: 99%
“…They also found that this situation negatively impacted communication effectiveness between doctor and patient. Although our study did not explore treatment quality, it is possible that this parameter was affected during the MCO given that time spent interacting with healthcare professionals affects treatment outcomes and patient satisfaction [95][96][97].…”
Section: Covid-19 Response Measures Among Healthcare Servicesmentioning
confidence: 99%
“…The physician's professional skill is essential to patient care quality that directly impacts the patient's feedback [26,28,50]. Related to the professional skills, the physician's response to the patient also influences the quality of care and health outcome that can be measured in patient feedbacks [26,27,[51][52][53]. Our study revealed the higher satisfaction among hospitalist's patients in communication skills, interpersonal skills, professionalism, and accessibility.…”
Section: Discussionmentioning
confidence: 66%
“…After a medical call to resolve the issue, it was found that doctors who took longer than 10 minutes per call were 4.14 times more likely to be nonhospitalists than hospitalists (95% CI, 3.15-5.44; P < 0.001). 18 In the Korean hospitalist system, the fee schedule is classified into type 1 (weekday-daytime model), type 2 (all week-daytime model), and type 3 (full-time model) according to the hospitalist's working hours. Ideally, hospitalists would care for patients 24 hours a day, but because the system is new, the number of hospitalists and reimbursements are still insufficient, making hospitals unsure of adopting the hospitalist system.…”
Section: Discussionmentioning
confidence: 99%